2023
DOI: 10.1590/0001-3765202320211486
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of the organotellurium 2-Phenylethynyl-Butyltellurium on the Drosophila melanogaster model

Abstract: 2-Phenylethynyl-Butyltellurium (PEBT) is a synthetic organotellurium compound that has shown various pharmacological properties on mammals without any signs of toxicity, but its effects on insects have not been reported before. Therefore, the aim of this study was to assess whether acute exposure to PEBT would promote an insecticidal effect against Drosophila melanogaster. The flies were exposed to three concentrations of PEBT (0.325 µmol L -1 , 1.300 µmol L -1 , and 5.200 µmol L -1 ) and a control solution (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…On the other hand, the increased AChE activity in larvae treated with FR may be linked to the insecticidal activity of this preparation. Bittencout and Souza [44] reported that 2-phenylethynyl-butyltellurium (PEBT), an insecticidal organotellurium compound, increased the AChE in the heads of Drosophila melanogaster. These authors called attention to a hypothesis that both decreases or increases in AChE activity can impact the locomotion of insects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increased AChE activity in larvae treated with FR may be linked to the insecticidal activity of this preparation. Bittencout and Souza [44] reported that 2-phenylethynyl-butyltellurium (PEBT), an insecticidal organotellurium compound, increased the AChE in the heads of Drosophila melanogaster. These authors called attention to a hypothesis that both decreases or increases in AChE activity can impact the locomotion of insects.…”
Section: Discussionmentioning
confidence: 99%